Cognitive Bias Modification for adolescents with substance use problems – Can serious games help?. (December 2015) - Boendermaker, Wouter J.; Prins, Pier J.M.; Wiers, Reinout W.
Abstract: Background and Objectives: Excessive use of psychoactive substances and resulting disorders are a major societal problem, and the most prevalent mental disorder in young men. Recent reviews have concluded that Cognitive Bias Modification (CBM) shows promise as an intervention method in this field. As adolescence is a critical formative period, successful early intervention may be key in preventing later substance use disorders that are difficult to treat. One issue with adolescents, however, is that they often lack the motivation to change their behavior, and to engage in multisession cognitive training programs. The upcoming use of serious games for health may provide a solution to this motivational challenge. Methods: As the use of game-elements in CBM is fairly new, there are very few published studies in this field. This review therefore focuses on currently available evidence from similar fields, such as cognitive training, as well as several ongoing CBM gamification projects, to illustrate the general principles. Results: A number of steps in the gamification process are identified, starting with the original, evidence-based CBM task, towards full integration in a game. While more data is needed, some steps seem better suited for CBM gamification than others. Based on the current evidence, several recommendations are made. Limitations: As the field is still in its infancy, further research is needed before firm conclusions can be drawn. Conclusions: Gamified CBM may be a promising way to reach at risk youth, but the term "game" should be used with caution. Suggestions are made for future research. Highlights: Serious games may help to motivate adolescents to do Cognitive Bias Modification (CBM) training. Several distinctions between serious game techniques are discussed. Recommendations for future research include exploring intrinsic vs. extrinsic motivation.